Application of half butterfly method in listing permutation - Karim, Sharmila; Mohd Darus, Maizon; Ibrahim, Haslinda (IP Publishing LLC, 2016)
A Half Butterfly Method is a new method introduced to construct the distinct circuits in complete graphs where used the concept of isomorphism. The Half Butterfly Method can be applied in the field of combinatorics such as in listing permutations of n elements.Thus, in this paper, we presented a permutation generation using Half Butterfly Method.